THE ROLE OF MOBILE APPLICATIONS AND AI IN CONTINUOUS GLUCOSE MONITORING: A COMPREHENSIVE REVIEW OF KEY SCIENTIFIC CONTRIBUTIONS (INTERNATIONAL JOURNAL OF ARTIFICIAL INTELLIGENCE IN MEDICINE (IJAIMED), 2023)
Continuous Glucose Monitoring (CGM) has transformed diabetes management by providing real-time glucose data through mobile apps. This article explores the integration of Artificial Intelligence (AI) into CGM technology, enabling personalized insights and improved treatment outcomes. Combining mobile apps with AI opens new avenues in diabetes care, promising enhanced quality of life for patients. With ongoing technological advancements, the potential for further breakthroughs in diabetes management is vast. We stand at the threshold of an exciting era in diabetes care, offering hope for a brighter future for millions of individuals with diabetes.